2015
DOI: 10.1016/j.ultsonch.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigations in physical mechanism of the oxidative desulfurization process assisted simultaneously by phase transfer agent and ultrasound

Abstract: This paper attempts to discern the physical mechanism of the oxidative desulfurization process simultaneously assisted by ultrasound and phase transfer agent (PTA). With different experimental protocols, an attempt is made to deduce individual beneficial effects of PTA and ultrasound on the oxidative desulfurization system, and also the synergy between the effects of PTA and ultrasound. Effect of PTA is more marked for mechanically stirred system due to mass transfer limitations, while intense emulsification d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 23 publications
0
34
2
Order By: Relevance
“…transesterification for the production of biodiesel, hydrolysis for degradation of compounds 85 including polymers, 86 acid or base-catalyzed methanolysis, 87 oxidative desulfurization, 88 demulsification 89 and nanoemulsification, 90 amongst others). transesterification for the production of biodiesel, hydrolysis for degradation of compounds 85 including polymers, 86 acid or base-catalyzed methanolysis, 87 oxidative desulfurization, 88 demulsification 89 and nanoemulsification, 90 amongst others).…”
Section: Ultrasound Phase Transfer Catalysismentioning
confidence: 99%
“…transesterification for the production of biodiesel, hydrolysis for degradation of compounds 85 including polymers, 86 acid or base-catalyzed methanolysis, 87 oxidative desulfurization, 88 demulsification 89 and nanoemulsification, 90 amongst others). transesterification for the production of biodiesel, hydrolysis for degradation of compounds 85 including polymers, 86 acid or base-catalyzed methanolysis, 87 oxidative desulfurization, 88 demulsification 89 and nanoemulsification, 90 amongst others).…”
Section: Ultrasound Phase Transfer Catalysismentioning
confidence: 99%
“…The experimental protocols with detail experimental summary of the present study are depicted in Table . The optimum values that is volume ratio of organic to aqueous phase and amount of H 2 O 2 was fixed as per our results of previous paper . The experiments were carried out in different oxidants system with combinations of formic acid, acetic acid, and/or phosphotungustic acid are as follows: (a) Acetic acid + H 2 O 2 + TBAB, (b) formic acid + H 2 O 2 + TBAB, (c) Phosphotungustic acid + Formic acid + H 2 O 2 + TBAB.…”
Section: Methodsmentioning
confidence: 99%
“…Generation of microemulsification through ultrasound enhances the liquid–liquid interfacial area that is important for cavitation of microbubble . In previous papers, it has been reported that ultrasound assisted oxidative desulfurization process can significantly improve the reaction efficiency under phase transfer agents (PTA) . The aim of this study is to investigate the physical and chemical effect of ultrasound on oxidative desulfurization of DBT with coupling of phosphotungstic acid and PTA.…”
Section: Introductionmentioning
confidence: 99%
“…If the static pressure is raised above acoustic pressure amplitude and the radial bubble motion transform into stable oscillatory one. In this case, all chemical effects of transient cavitation are eliminated [12,37,38], and the system resembles a mechanically stirred mixed system. It should be noted that the ultrasound wave phenomenon remains unaffected by static pressure.…”
Section: Variation In Static Pressure Of the Mediummentioning
confidence: 99%